Seventeen Fans Weaving Parasocial Web through Media Multiplexity - Swastika, Gabriela Laras Dewi; Njotoharsojo, Sasha Kurnia (Universitas Mercu Buana, 2025)
The South Korean entertainment industry, particularly K-Pop, uses social media to connect the idols to their fans worldwide. This strategy is also used by Seventeen. K Pop idols Seventeen through their agencies manage continuous interactions, making fans believe they are close and know their idol well. The use of platforms also emphasizes the media multiplexity to connect with their mediated parasocial interaction. This phenomenon raises the question of how fandom Carat, the group of fans of Seventeen, weaves the parasocial interaction on Seventeen’s Youtube and Weverse. This research investigates the parasocial interaction done by Carat on Seventeen's Youtube and Weverse and the web of media or known as media multiplexity which emerges within the activity of idolization. This research uses a quasi-qualitative approach. Data collection techniques used in this study are interviews and document study. Based on the results, we found that Carat became their identity presented in parasocial interactions. Carat conducted mediated parasocial interactions on Youtube and Weverse. Through the media multiplexity Carat created a sense of comfort and familiarity coming from repeated exposure to Seventeen’s media and content. The next finding is that Carat felt that they were not close to Seventeen if they didn’t actively weave and connect their parasocial interaction.